Peer support for parents of children with chronic disabling conditions: a systematic review of quantitative and qualitative studies - Shilling, Val; Morris, Christopher; Thompson‐Coon, Jo; Ukoumunne, Obioha; Rogers, Morwenna; Logan, Stuart (Developmental medicine and child neurology, 2013)
AIM To review the qualitative and quantitative evidence of the benefits of peer support for parents of children with disabling conditions in the context of health, well‐being, impact on family, and economic and service implications. Method We comprehensively searched multiple databases. Eligible studies evaluated parent‐to‐parent support and reported on the psychological health and experience of giving or receiving support. There were no limits on the child's condition, study design, language, date, or setting. We sought to aggregate quantitative data; findings of qualitative studies were combined using thematic analysis. Qualitative and quantitative data were brought together in a narrative synthesis. Results Seventeen papers were included: nine qualitative studies, seven quantitative studies, and one mixed‐methods evaluation. Four themes were identified from qualitative studies: (1) shared social identity, (2) learning from the experiences of others, (3) personal growth, and (4) supporting others. Some quantitative studies reported a positive effect of peer support on psychological health and other outcomes; however, this was not consistently confirmed. It was not possible to aggregate data across studies. No costing data were identified. Conclusion Qualitative studies strongly suggest that parents perceive benefit from peer support programmes, an effect seen across different types of support and conditions. However, quantitative studies provide inconsistent evidence of positive effects. Further research should explore whether this dissonance is substantive or an artefact of how outcomes have been measured.